2011
DOI: 10.29309/tpmj/2011.18.01.1878
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Peptic Ulcer

Abstract: Objectives: To evaluate the epidemiology of peptic ulcer perforation in Armed Forces and further management / outcome of the patients. Methods: Data of 36 patients with perforated peptic ulcer collected. This data was analyzed on SPSS 13. Period and Setting: CMH Rawalpindi from Jan 1979 to July 1981, Jan 1985 to Dec 1987 and Jan 2001 to Dec 2003. Results: Out of 36 patients 35 were male and only one was female. Twenty four (67%) were between 31-50 years. No past history was taken from eight (22%) patients. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Our study concurred with findings in Ghana [ 24 ] and Nigeria [ 25 ]. However, this was in contrast to findings of Bhardwaj [ 26 ], Khan [ 27 ] and a Rwandese study by Rickard [ 28 ], in which duodenal perforations were over represented. In addition, our findings were incongruent to those from Tanzania [ 15 ], Kenya [ 29 ] and Southern Sudan [ 30 ] where the ratio of gastric to duodenal perforations were 1:12.7, 1:11.5 and 1:25 respectively.…”
Section: Discussioncontrasting
confidence: 92%
“…Our study concurred with findings in Ghana [ 24 ] and Nigeria [ 25 ]. However, this was in contrast to findings of Bhardwaj [ 26 ], Khan [ 27 ] and a Rwandese study by Rickard [ 28 ], in which duodenal perforations were over represented. In addition, our findings were incongruent to those from Tanzania [ 15 ], Kenya [ 29 ] and Southern Sudan [ 30 ] where the ratio of gastric to duodenal perforations were 1:12.7, 1:11.5 and 1:25 respectively.…”
Section: Discussioncontrasting
confidence: 92%
“…Over 75 percent of duodenal perforations happened before the age of 50. We highlight that gastroduodenal ulcers share a similar pathophysiology, particularly with H. pylori infestation 17 which was more prevalent in younger patients from lower socioeconomic groups, 17 despite the fact that we do not have a good reason for this shifting epidemiological profile. Since up to three out of every five patients in this research had no prior dyspeptic history, it has been shown that perforation may be the earliest sign of peptic ulcer disease.…”
Section: Resultsmentioning
confidence: 80%
“…Several additional African studies demonstrate a majority of duodenal perforation, despite a prior research from a city hospital in Ghana having revealed a similar conclusion 16 . We highlight that gastroduodenal ulcers share a similar pathophysiology, particularly with H. pylori infestation, 17 which was more prevalent in younger patients from lower socioeconomic groups, 24,25 despite the fact that we do not have a good reason for this shifting epidemiological profile. Studies from Southern and Northern Nigeria show that urease culture tests for antral biopsies had a high incidence of 81.4% and over 90% with serological testing among individuals with dyspepsia.While H. pylori testing was not accessible in our facility for this investigation, all patients with perforated ulcers underwent H. pylori eradication medication.…”
Section: Discussionmentioning
confidence: 78%